Enablers to achieve zero hunger through IoT and blockchain technology and transform the green food supply chain systems. (15th June 2023) - Kumar, Mukesh; Choubey, Vikas Kumar; Raut, Rakesh D.; Jagtap, Sandeep
Abstract: Food security necessitates a multifaceted strategy, ranging from social protection to providing healthy food. Change in existing food systems is needed to create a more equitable and sustainable society. Hunger is one of the significant challenges in the world that arise due to food insecurity, bad quality, food waste, and losses that leads to damage of public health. The implementation of green food supply chain management (GFSCM) practices in the food supply chain helps in lowering food wastage, carbon emissions, food quality, and safety. To strengthen food security/safety and quality, digital transformation of the supply chain is required, and IoT and blockchain can help in achieving this. Digital transformation of GFSCM has helped to improve food security, safety and quality control. This study identifies modern enablers of food security, safety and quality that transform the GFSCM through Internet of things (IoT) and blockchain to reduce hunger. Zero hunger goal is far behind in India as India reported 117th rank in hunger index, indicating an urgent need to study the digital transformation in green food supply chain towards achieving food quality and security. In this study twelve enablers out of 16 suggested in earlier literatures has been selected and reconfirmed with the feedback of seventeen academia and Industrial experts from Indian food supply chain. We used a two-step combined Interpretive Structural Modeling (ISM) and Analytical Network Process (ANP) technique to examine the enablers contextual interrelationships and significance weights. Findings reveal that IoT and blockchain technologies are the main actuators of the contemporary GFSCM enabling system. ISM provides eight core enablers system that can transform the GFSCM digitally to achieve food quality and security along with achieving zero hunger (SDG2). Inventory management is the least ranked enabler, whereas IoT and blockchain are the top two. Towards achieving zero hunger, some management, theoretical, and policy implications have been suggested. Highlights: Digital technologies in GFSCM help improve food security. This study identifies modern enablers of GFSCM for food security. Twelve GFSCM enablers of food security from literature and expert discussion. A two-step integrated ISM and ANP methodology has been utilized.